Marcel and Ricoeur’s Understanding of Being as Incarnate Existence: Against the Possible Contemporary Return of the Mind-body Dualism - Verhoef, Anné; Janse van Rensburg, Zander (Phronimon, 2022)
In this article, we indicate some examples of the possible contemporary return of the mind-body dualism. Aspects of contemporary culture, like the influence of brain-computer interface (BCI) or brain-machine interface (BMI), neuroscience projects, and the popularity of sci-fi series and movies that visualise the separation of consciousness from our bodies, are discussed. Only a few of these examples are indicated as introductory to emphasise the need to think again about the importance of some of the strongest philosophical arguments against this dualism. It is in this regard that we will focus on the philosophies of Gabriel Marcel and Paul Ricoeur. Of specific concern for us in this article is Marcel’s influence on Ricoeur in his fundamental rejection of the mind-body dualism. This article’s unique contribution lies, then, in the fact that it analyses and reveals this influence of Marcel on Ricoeur, especially with regards to their shared understanding of embodied being, or incarnate existence, as opposed to a body-mind dualism. This investigation of how Marcel influenced Ricoeur provides a better understanding of: i) Ricoeur’s account of embodied being; ii) Marcel’s philosophy and concept of incarnate existence as being; and finally, iii) the importance of rejecting a mind-body dualism for our contemporary thought and living